Assessment of health-related quality of life among Asthmatic patients: The need for structured pharmaceutical care delivery system in Pakistan - Madeeha Malik; Adeela Khan; Azhar Hussain; Ayisha Hashmi (Journal of Pharmacy and Bioallied Sciences, 2017)
Asthma is considered as one of the most common chronic diseases in the world. As a result of serious physical, social, and psychological complications, asthma can reduce health-related quality of life (HRQoL). The present study was designed to assess the HRQoL including physical health, general health perception, emotional health, psychological health, and social functioning of asthmatic patients in Pakistan. A descriptive cross-sectional study design was used. Setting was public and private healthcare facilities. SF-36 was self-administered to a sample of 382 asthmatic patients. After data collection, data were clean coded and entered in SPSS version 21.0. Skewness test was performed and histograms with normal curves were used to check the normal distribution of data. Descriptive statistics comprising of frequency and percentages was calculated. The non-parametric tests including Mann–Whitney and Kruskal–Walis (P ≥ 0.05) were performed to find out the difference among different variables. The results of the current study highlighted a significant impact on several domains of HRQoL for asthmatic patients. Lowest scores for HRQoL were observed in the domain of general health (27.74 ± 18.29) followed by domain of mental health (38.26 ± 20.76) whereas highest scores were observed in the domain of social functioning (45.64 ± 25.89). The results of the study concluded that asthmatic patients in Pakistan had poor HRQoL. Well-structured pharmaceutical care delivery in the healthcare facilities can contribute toward better patient knowledge and management and can ultimately improve the HRQoL of asthma patients.